2008
DOI: 10.1519/jsc.0b013e318185f0df
|View full text |Cite
|
Sign up to set email alerts
|

Intersession Reliability of Vertical Jump Height in Women and Men

Abstract: The purpose of the present study was to investigate the intersession reliability of vertical jump height in women and men recorded from a contact mat. Thirty-five women and 35 men performed four testing sessions across a 4-week period, with each session separated by 1 week. Within each testing session, subjects completed three countermovement vertical jumps (CMJs) for maximum height. Reliability statistics were calculated using the highest jump (HIGH) and also from the mean of all three jumps (3 MEAN) during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 6 publications
5
69
0
5
Order By: Relevance
“…This is also evident in the golf swing 18 and it is possible that increased leg power, as inferred by jumping assessment, aids rapid RFD, 19 influencing CHS (Read et al, 2013). 20 The study demonstrated that following eight weeks of plyometric training, the intervention group 21 significantly increased their physical performance in the SVJ, SBJ, and KRT, when compared to the 22 control group (10.8%, 10.2%, 22.9%, respectively). The control group however, also displayed 23 significant differences (3.0%, 3.2%, 3.5% respectively) between pre and post-tests in these variables, 24 but this is likely explained by the typical error of these assessment methods.…”
Section: Results: 21 [Table 2 Here] 22mentioning
confidence: 89%
“…This is also evident in the golf swing 18 and it is possible that increased leg power, as inferred by jumping assessment, aids rapid RFD, 19 influencing CHS (Read et al, 2013). 20 The study demonstrated that following eight weeks of plyometric training, the intervention group 21 significantly increased their physical performance in the SVJ, SBJ, and KRT, when compared to the 22 control group (10.8%, 10.2%, 22.9%, respectively). The control group however, also displayed 23 significant differences (3.0%, 3.2%, 3.5% respectively) between pre and post-tests in these variables, 24 but this is likely explained by the typical error of these assessment methods.…”
Section: Results: 21 [Table 2 Here] 22mentioning
confidence: 89%
“…The best score (highest: CMJ, SJ, MBT, 6 s Cycle, lowest: RMS) was used for data analysis, as this has shown to significantly increase intersession reliability as opposed to means [22]. Changes were assessed across all conditions using a repeated measures ANOVA through SPSS for Windows, release 22.0 (SPSS, IBM Corporation, Armonk, NY, USA).…”
Section: Resultsmentioning
confidence: 99%
“…For all measurements, the highest CMJ was used from each trial for each condition to reduce variability (18).…”
Section: Methodsmentioning
confidence: 99%